What Do You Have in Mind? Measures to Assess Mental State Reasoning in Neuropsychiatric Populations - Eddy, Clare M. (Frontiers in Psychiatry, 2019)
Social interaction is closely associated with both functional capacity and wellbeing. Previous research has not only revealed evidence of social dysfunction in individuals with a wide range of psychiatric and neurological disorders, but has also generated an abundance of potential measures for assessing social cognition. This review explores the most popular measures used within neuropsychiatric populations to investigate the ability to recognise or reason about the mental states of others. Measures are also critically analysed in terms of strengths and limitations to aid task selection in future clinical studies. The most frequently applied assessment tools use verbal/visual or audiovisual forms of presentation, and assess recognition of mental states from facial features, self-rated empathy, the understanding of other’s cognitive mental states such as beliefs and intentions, or the ability to combine knowledge of other’s thoughts and emotions in order to understand subtle communications or socially inappropriate behaviour. Key weaknesses of previous research include limited investigation of relationships with clinical symptoms, and under-utilisation of measures of everyday social functioning which offer a useful counterpart to traditional ‘lab’ tasks. Future studies should aim to carefully select measures based not only on the range of skills to be assessed, but also taking into account potential difficulties with interpretation and the need to gain insight into the application of social cognitive skills as well as ability per se. Some of the best measures include those with well-matched control trials (e.g. Yoni Task) or restrict the influence of verbal deficits (e.g. intentions comic strip task), elicit spontaneous mentalizing (e.g. Animations Task) and possess greater ecological validity (e.g. Movie for the Assessment of Social Cognition). Social cognitive research within psychiatric populations will be further enhanced through the development of more closely matched control tasks, and the exploration of relationships between task performance, medication, strategy use and broader emotional and motor functions.